Risk factors for and outcomes of poststroke pneumonia in patients with acute ischemic stroke treated with mechanical thrombectomy - Zhang, Ping; Chen, Lei; Jiang, Yi; Yuan, Hui; Zhu, Xuan; Zhang, Minmin; Wu, Tao; Deng, Benqiang; Yang, Pengfei; Zhang, Yongwei; Liu, Jianmin (Frontiers in Neurology, 2023)
Objective: To assess the risk factors for poststroke pneumonia (PSP) and its association with outcomes in patients with acute ischemic stroke (AIS) due to large artery occlusion treated with mechanical thrombectomy (MT). Methods: Consecutive patients with AIS who underwent MT from January 2019 to December 2019 in the stroke center of Changhai Hospital were identified retrospectively. All of the patients were evaluated for the occurrence of PSP while in the hospital, and their modified Rankin scale (mRS) scores were assessed 90 days after having a stroke. Logistic regression analysis was conducted to determine the independent predictors of PSP, and the associations between PSP and clinical outcomes were analyzed. Results: A total of 248 patients were enrolled, of whom 33.47% (83) developed PSP. Logistic regression analysis revealed that body mass index (BMI) (unadjusted odds ratio [OR] 1.200, 95% confidence interval [CI] 1.038-1.387; P = 0.014), systemic immune-inflammation index (SII) (OR 1.001, 95% CI 1.000-1.002; P=0.003), dysphagia (OR 9.498, 95% CI 3.217-28.041; p<0.001) and intubation after MT (OR 4.262, 95% CI 1.166-15.581; P=0.028) were independent risk factors for PSP. PSP was a strong predictor of clinical outcomes: it was associated with functional independence (mRS score≤2) (OR 0.104, 95% CI 0.041-0.260; P < 0.001) and mortality at 90 days (OR 3.010, 95% CI 1.068-8.489; P=0.037). Conclusions: More than one in three AIS patients treated with MT developed PSP. Dysphagia, intubation, higher BMI and SII were associated with PSP in these patients. AIS patients who develop PSP are more likely to experience negative outcomes. The prevention and identification of PSP is necessary to reduce mortality and improve clinical outcomes.